A Case of the 7p22.2 Microduplication: Refinement of the Critical Chromosome Region for 7p22 Duplication Syndrome - Cox, Devin M.; Butler, Merlin G. (Journal of Pediatric Genetics, 2015)
We report a 14-year-old Hispanic male with a microduplication of the chromosome 7p22.2 band detected through microarray analysis. He had a history of developmental delay and mild intellectual disability, asthma, myopia, proportionate short stature, dysmorphic features, and Achilles tendon release. This appears to be the first report of a patient with a microduplication of only the chromosome 7p22.2 band and is now the smallest reported duplication to date to include features in common with the chromosome 7p22 duplication syndrome.
Keywords: 7p22.2 duplication; microarray analysis; dysmorphic features; mild intellectual disability